2017
DOI: 10.1186/s12885-017-3444-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview on the surgical management of secondary lymphedema of the upper and lower extremities related to prior oncologic therapies

Abstract: Secondary lymphedema of the upper and lower extremities related to prior oncologic therapies, including cancer surgeries, radiation therapy, and chemotherapy, is a major cause of long-term morbidity in cancer patients. For the upper extremities, it is most commonly associated with prior oncologic therapies for breast cancer, while for the lower extremities, it is most commonly associated with oncologic therapies for gynecologic cancers, urologic cancers, melanoma, and lymphoma. Both non-surgical and surgical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 75 publications
2
98
0
Order By: Relevance
“…Physiologic procedures such as LVA and VLNT have been described in the treatment of lymphedema refractory to conservative therapy. (Carl et al, ; Garza 3rd et al, ; Kung, Champaneria, Maki, & Neligan, ) Physiologic procedures have yielded effective and enduring results in the treatment of both primary and secondary lymphedema (Boccardo et al, ; Campisi et al, ). Its efficacy in primary lymphedema, however, is controversial (Beaulac, McNair, Scott, LaMorte, & Kavanah, ; Chang, ; Demirtas, Ozturk, Yapici, & Topalan, ; Gloviczki et al, ; Grant et al, ; Hara et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologic procedures such as LVA and VLNT have been described in the treatment of lymphedema refractory to conservative therapy. (Carl et al, ; Garza 3rd et al, ; Kung, Champaneria, Maki, & Neligan, ) Physiologic procedures have yielded effective and enduring results in the treatment of both primary and secondary lymphedema (Boccardo et al, ; Campisi et al, ). Its efficacy in primary lymphedema, however, is controversial (Beaulac, McNair, Scott, LaMorte, & Kavanah, ; Chang, ; Demirtas, Ozturk, Yapici, & Topalan, ; Gloviczki et al, ; Grant et al, ; Hara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reported incidence in the literature can range between 7.6 and 49% (Meneses & McNees, ), but seems to be trending down due to newer surgical and radiation techniques for breast cancer treatment. Conversely, LLL most commonly occurs secondary to the treatment of gynecologic or urologic cancers, melanoma and lymphoma, as well as from inguinal, pelvic and para‐aortic lymph node dissections (Garza 3rd et al, ). Earlier studies reported 69% of LLL in patients with vulvar cancer, but the advent of newer treatments has reduced it to nearly 30% (Gould et al, ; Podratz, Symmonds, Taylor, & Williams, ).…”
Section: Introductionmentioning
confidence: 99%
“…After the approval from the institutional review board, all patients who underwent the CMST in the form of Charles,' Homan's, VLNT, and toe management were identified. The patients had to have met the following criteria to receive this treatment: (1) ISL stage III LEL with limitation of mobility and activities of daily living, (2) Between July 2013 and July 2017, a retrospective review of a prospectively collected database was conducted. In addition to patient demographics, precipitating pathology, preoperative duration of symptoms, conservative treatment, and episodes of infection were noted.…”
Section: Methodsmentioning
confidence: 99%
“…While it continues to be an essential pillar of any treatment plan, surgical treatment of lymphedema has enjoyed a renewed interest over the last decade. This is particularly true for the physiologic procedures such as vascularized lymph node transfer (VLNT) and lymphovenous anastomosis (LVA) . By facilitating proximal lymph flow, a basic pathophysiologic mechanism can be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation